Is a cross-connector beneficial for single level traditional or cortical bone trajectory pedicle screw instrumentation? - Frédéric Cornaz (Public Library of Science (PLoS), 2021)
The cortical bone trajectory (CBT) has been introduced with the aim of better screw hold, however, screw-rod constructs with this trajectory might provide less rigidity in lateral bending (LB) and axial rotation (AR) compared to the constructs with the traditional trajectory (TT). Therefore, the addition of a horizontal cross-connector could be beneficial in counteracting this possible inferiority. The aim of this study was to compare the primary rigidity of TT with CBT screw-rod constructs and to quantify the effect of cross-connector-augmentation in both. Spines of four human cadavers (T9 -L5) were cropped into 15 functional spine units (FSU). Eight FSUs were instrumented with TT and seven FSUs with CBT pedicle screws. The segments were tested in six loading directions in three configurations: uninstrumented, instrumented with and without cross-connector. The motion between the cranial and caudal vertebra was recorded. The range of motion (ROM) between the CBT and the TT group did not differ significantly in either configuration. Cross-connector -augmentation did reduce the ROM in AR (16.3%, 0.27°, p = 0.02), LB (2.9%, 0.07°, p = 0.03) and flexion-extension FE (2.3%, 0.04°, p = 0.02) for the TT group and in AR (20.6%, 0.31°, p = 0.01) for the CBT-group. The primary rigidity of TT and CBT single level screw-rod constructs did not show significant difference. The minimal reduction of ROM due to cross-connector-augmentation seems clinically not relevant. Based on the findings of these study there is no increased necessity to use a cross-connector in a CBT-construct.